LAPAR Sulsel's Action In Building Political Literacy In Makassar City Communities - Riya Anjarsari (Asian Journal of Social and Humanities, 2023)
LAPAR Sulsel that actively contributes to the development of political understanding and participation at the local level. Political education is a key factor in enhancing people's political participation and developing inclusive democracies. Methodology of this study is descriptive and qualitative. The researchers conducted in-depth interviews with LAPAR Sulsel staff, community members and other key stakeholders in the Makassar city area. Researchers also performed participatory observations and document analysis to collect comprehensive data. Research results show that LAPAR Sulsel has taken an important step in the development of civic education for the people of Makassar city. By providing easily accessible information, advice, training, debates and political awareness campaigns, the company has helped people better understand complex political processes and increase political participation. This has resulted in increased participation in elections, greater knowledge of political rights and an improved ability to make better informed political decisions. General conclusion of this study is that the company contributed to the development of people's political understanding, increased political participation, and made a great contribution to the development of local democracy.